PENGARUH RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Wardani, Runy Dwi; Yando, Agus Defri (LPPM Universitas Putera Batam, 2020)
This research aims to determine whether liquidity and profitability ratios effect both partially and simultaneously the profit growth of mining companies listed on the Indonesia Stock Exchange. The company’s main goal is to maximize profits. For companies, profits are needed because they are beneficial for the survival of the company. One of the company’s perfomance parameters is profit. The profits generated by the company experience changes in profits each year so that it can effect investment decisions on investors. Profit growth is an increase or decrease in profit per year. The ratio used in this research is the current ratio, net profit margin, gross profit margin. The analysis technique used in this study is multiple linear regression analysis. The conclusion is the results of the study show that partially the current ratio and net profit margin influence the profit growth with the significance value of each ratio namely the current ratio of 0,007 and net profit margin of 0,016. While the gross profit margin partially has no effect on profit growth with a significance value of 0,855 gross profit margin.simultaneously cureent ratio, net profit margin, gross profit margin significantly influence profit growth with a significance value of 0,001.